Effect Of Chirality On The Phases In Thin-Film Antiferroelectric Liquid Crystals - Lum, Chia Yuee (2011)
The discrete phenomenological Landau theory is employed to investigate the effect of chirality on the freely suspended antiferroelectric smectic thin film liquid crystals. Smectic systems which consist of three- and four- layered smectic liquid crystals are chosen to represent odd and even layers system. This discrete model considers the interaction energy of the smectic system as a sum of energy of each interacting layer. Interactions are divided into two parts, the interaction within layer and interactions between layers. Interactions between layers are considered only up to next nearest neighbours while chiral interaction is considered to be significant between nearest neighbour only. The studies has two parts. First part of the studies concerns the effect of chirality on the stability of the orthogonalstructure. Stability of system is analyzed through the Landau-Khalatnikov theory. Our results have shown that chirality increases the transition temperature of the orthogonalto the tilted structures at the lower temperature.